Spontaneous Intracranial Hypotension Treated with a Targeted CT-Guided Epidural Blood Patch - Inês Correia; Inês Brás Marques; Rogério Ferreira; Miguel Cordeiro; Lívia Sousa (Case Reports in Medicine)
Spontaneous intracranial hypotension (SIH) is an important cause of new daily persistent headache. It is thought to be due to spontaneous spinal cerebrospinal fluid (CSF) leaks, which probably have a multifactorial etiology. The classic manifestation of SIH is an orthostatic headache, but other neurological symptoms may be present. An epidural blood patch is thought to be the most effective treatment, but a blind infusion may be ineffective. We describe the case of a young man who developed an acute severe headache, with pain worsening when assuming an upright posture and relief gained with recumbency. No history of previous headache, recent cranial or cervical trauma, or invasive procedures was reported. Magnetic resonance imaging showed pachymeningeal enhancement and other features consistent with SIH and pointed towards a cervical CSF leak site. After failure of conservative treatment, a targeted computer tomography-guided EBP was performed, with complete recovery.